(untitled) (Confluenţe Bibliologice, 2023)
The article presents information about the Venn Diagram, which is a graphic method used to represent the relationships between different sets or groups of elements. The purpose of the research is to answer some questions regarding the use of this diagram in the library, demonstrating the advantages and disadvantages of its use.